2016
DOI: 10.1038/ncomms12545
|View full text |Cite
|
Sign up to set email alerts
|

A moving contact line as a rheometer for nanometric interfacial layers

Abstract: How a liquid drop sits or moves depends on the physical and mechanical properties of the underlying substrate. This can be seen in the hysteresis of the contact angle made by a drop on a solid, which is known to originate from surface heterogeneities, and in the slowing of droplet motion on deformable solids. Here, we show how a moving contact line can be used to characterize a molecularly thin polymer layer on a solid. We find that the hysteresis depends on the polymerization index and can be optimized to be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 39 publications
0
41
0
Order By: Relevance
“…The principle of measurement shown in Figure 2a is simple: the capillary rise is measured while the sample surface is plunged in or withdrawn from a liquid bath at a constant, controlled velocity [12,[19][20][21][22][23][24]. With careful implementation of this so-called "dip-coater" geometry, a remarkable precision and range in the measured contact line dynamics can be obtained.…”
Section: Measuring Contact Line Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…The principle of measurement shown in Figure 2a is simple: the capillary rise is measured while the sample surface is plunged in or withdrawn from a liquid bath at a constant, controlled velocity [12,[19][20][21][22][23][24]. With careful implementation of this so-called "dip-coater" geometry, a remarkable precision and range in the measured contact line dynamics can be obtained.…”
Section: Measuring Contact Line Dynamicsmentioning
confidence: 99%
“…In this section we briefly recall a simple model of viscoelastic dissipation in a pseudo-brush, which was developed and tested for one particular good solvent [12] but which we will use here to compare the dynamics between different N and different liquids.…”
Section: Viscoelastic Dissipation In a Pseudo-brushmentioning
confidence: 99%
See 1 more Smart Citation
“…The droplets deform the soft solid into a "wetting ridge" that moves along with the contact line, and thus also probe the viscoelastic response of the polymer [21,26]. It has been shown that the response of nanometer scale polymers grafted or adsorbed at a surface presents a scaling law consistent with the picture emerging from statistical physics [72]. However, in order for droplets to be fully useful as a rheological tool, one must have a perfect theoretical understanding of the processes at work.…”
Section: Introductionmentioning
confidence: 80%
“…From an engineering perspective, there is a continued effort in designing surfaces with low contact angle hysteresis for purposes of hydrophobicity, self-cleaning, or anti-fouling coatings [91,92]. Recently, wetting of soft surfaces has generated a large interest: The liquid-like surface properties of reticulated polymer networks and brushes can offer nearly hysteresis-free substrates [72,80]. However, despite the absence of hysteresis, drops on these soft surfaces do exhibit a stick-slip motion when forced to spread beyond a threshold velocity as observed in chapter 2 and [33,35,79].…”
Section: Introductionmentioning
confidence: 99%